2013
DOI: 10.1051/0004-6361/201220692
|View full text |Cite
|
Sign up to set email alerts
|

Single degenerate supernova type Ia progenitors

Abstract: Context. There is general agreement that supernovae Ia correspond to the thermonuclear runaway of a white dwarf that is part of a compact binary, but the details of the progenitor systems are still unknown and much debated. One of the proposed progenitor theories is the single-degenerate channel in which a white dwarf accretes from a companion, grows in mass, reaches a critical mass limit, and is then consumed after thermonuclear runaway sets in. However, there are major disagreements about the theoretical del… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 74 publications
1
74
2
Order By: Relevance
“…The differences that they find are caused by differences in the inherent assumptions in the codes, such as the initial-final mass relation, helium star evolution, the stability criterion of Roche-lobe overflowing stars and the mass transfer rate. In addition, Bours et al (2013) show that the lack of understanding of the retention efficiency of WDs gives an integrated rate of the SD channel which varies between <10 −7 and 1.5 × 10 −4 M −1 .…”
Section: Other Uncertainties In the Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The differences that they find are caused by differences in the inherent assumptions in the codes, such as the initial-final mass relation, helium star evolution, the stability criterion of Roche-lobe overflowing stars and the mass transfer rate. In addition, Bours et al (2013) show that the lack of understanding of the retention efficiency of WDs gives an integrated rate of the SD channel which varies between <10 −7 and 1.5 × 10 −4 M −1 .…”
Section: Other Uncertainties In the Resultsmentioning
confidence: 97%
“…For this and other reasons, the retention efficiency of WDs is uncertain and several models exist which describe this efficiency , and reference therein). Rather than investigating the effect of different retention efficiencies, as was done by Bours et al (2013), we consider an extreme possibility where all mass transferred to the WD by RLOF remains on the WD and is burnt into carbon and oxygen (model F 1 ). We do not consider this unlimited accretion onto a WD as a realistic model, but it represents 1000 10000 Time ( an upper limit to the SD channel.…”
Section: Unlimited Accretion Onto Wdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other observational constraints, such as cluster SN Ia rates, have recently found values closer to 2×10 −3 M −1 (Maoz & Badenes 2010)-still consistent within the large error bars. However, theoretical predictions from binary population synthesis models are frequently lower by factors of 10 or more (Bours et al 2013). This discrepancy between theory and observation remains one of the key concerns in the SN Ia progenitor problem.…”
Section: Dtd Model Fitting Resultsmentioning
confidence: 99%
“…We find this scenario questionable, both with respect to its realization and its stability, although attractive if the main goal is to match the observed SN Ia rates with theoretical modelling based solely on the single-degenerate scenario. In a recent paper Bours et al (2013) demonstrated the strong dependence on the predicted SN Ia rates on the wind-stripping effect and on the mass accumulation (retention) efficiency of the accreting WD. and Liu et al (2010) studied the helium star donor channel for SNe Ia.…”
Section: Comparison To Previous Workmentioning
confidence: 98%